2022
DOI: 10.3389/fonc.2022.1024772
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between telomere length and the prognosis of breast cancer based on estrogen receptor status: A Mendelian randomization study

Abstract: ObjectiveTo identify the relationship between telomere length and the prognosis of breast cancer with different status of estrogen receptor (ER).MethodsWe collected single nucleotide polymorphisms (SNPs) associated with telomere length and breast cancer prognosis from the MRCIEU GWAS database and the dataset of a large meta-analysis conducted by the Breast Cancer Association Consortium (BCAC), respectively. The relationship was identified using inverse-variance weighted (IVW), MR-Egger, weighted median, penali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In contrast, some epidemiological studies reported telomere lengthening with adverse health outcomes such as breast cancer (Y. Li & Ma, 2022), gastric cancer (Z. Wang et al, 2018), and lung cancer (Doherty et al, 2018; Tsatsakis et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, some epidemiological studies reported telomere lengthening with adverse health outcomes such as breast cancer (Y. Li & Ma, 2022), gastric cancer (Z. Wang et al, 2018), and lung cancer (Doherty et al, 2018; Tsatsakis et al, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…CTC1 deletion caused defective telomere replication, resulting in catastrophic telomere loss [ 38 ]. Telomere length is significantly negatively correlated with the prognosis of breast cancer patients [ 39 ]; the better prognosis of cluster 2 may be attributed to the telomere length maintained by these telomere length-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an IV screening using the "TwoSampleMR" R package [74,78,79] to obtain independent IVs that affect lipoprotein levels in various gut microbiota data sets. The parameters used were as follows: p1 = 5 × 10 −8 (genetic variants must exhibit a strong association with the exposure), clump = TRUE, r 2 = 0.01, kb = 5000 (IVs with linkage disequilibrium were removed to ensure the independence of the selected genetic variations) [80,81]. A comprehensive screening process was conducted on 129 potential datasets to identify IVs for exposure, with their corresponding GWAS IDs ranging from "EBI-A-GCST90016959" to "EBI-A-GCST90017087" (Table S1).…”
Section: Exposure Datamentioning
confidence: 99%